Psychological bias in the teaching of English in higher education (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about the importance of psychological effects, factors and its role in language teaching; using and selecting suitable techniques in foreign language classes in order to improve learners’ communicative competences, motivation both effectively and smoothly in teaching and learning process.